Pelatihan dan Pendampingan “Penguatan Nilai – Nilai Pemasaran dan Kewirausahaan pada Siswa Putri SMK Taruna Jaya” - Vembri Aulia Rahmi; Ifahda Pratama Hapsari; Hadi Ismanto; Beni Dwi Komara (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
This community service is intended to introduce marketing and entrepreneurship values in the form of mentoring to female students in vocational schools which are expected to foster creativity and create positive attitudes in life. Community service methods include: socialization and lectures. Marketing training teaches students how to carry out marketing activities. Meanwhile, understanding entrepreneurship teaches students to interpret the business process and changing the value of an object or material into benefits. Socialization by introducing methods, tools for marketing. The development of the digital world provides opportunities to take advantage of available opportunities by using digital devices. Female students' understanding of marketing values in the digital era supports teaching and learning activities and students become responsive to environmental changes and are able to utilize digital devices for useful information. Entrepreneurial values teach students to do innovative things. Apart from technological developments in implementing marketing values and entrepreneurial practices, through lectures on how to wisely use digital media. Guidance to students regarding positive activities, such as product marketing and creativity upholds an entrepreneurial culture in schools.